Strategi Manajemen Pemasaran Digital dalam Menarik Minat Generasi Z - Rendi Maulana Akbar; Sopi Afrilia; Tika Wulandari; Sri Mulyeni (Pusat Riset dan Inovasi Nasional, 2026)
The development of technology in the digital era has significantly altered consumer behavior, particularly for Generation Z, who are known as digital natives. This group possesses unique characteristics, highly relying on social media to seek product information before making purchasing decisions. This study aims to analyze digital marketing management strategies through social media in enhancing brand engagement and loyalty among Generation Z consumers, as well as to identify the key determinants of its success. The research method employed is descriptive qualitative, utilizing literature review as the data collection technique across prior scientific sources. The analysis reveals that the implementation of digital marketing strategies based on visual content and short-form videos on platforms such as TikTok and Instagram is proven to be highly effective in capturing the audience's attention rapidly. In addition to content format, collaboration with highly credible influencers and the application of authentic, responsive two-way communication serve as the main pillars in building emotional proximity and trust among young consumers. Operationally, this strategy offers cost efficiency and a broader market reach. The conclusion of this study emphasizes that the optimal integration between management information systems and interactive, adaptive communication approaches toward digital trends is the main key to winning the market and sustaining the long-term loyalty of Generation Z.